Conservation on the high seas : harmonizing international regimes for the sustainable use of living resources - Borg, Simone (New horizons in environmental and energy law, 2012)
This timely book discusses various international norms that qualify the right, which all states have to access and exploit living resources in marine areas beyond national jurisdiction, in order to promote the conservation of such species